Developing equitable selection criteria for talent development programmes in inequitable contexts - Reeves, Megan Moya; Mashiloane, Landi; Bowman, Brett; Richards, Zena; Koen, Jennifer (South African Journal of Higher Education, 2016)
This paper explores the challenges of designing equitable selection criteria for a pre-university ‘talent development’ programme for high school learners from disadvantaged communities. It is argued that by giving due consideration to personal and environmental factors, it becomes possible to more reliably assess academic talent in inequitable contexts. The authors suggest that the experiences of the Go to University to Succeed (GUTS) programme in selecting learners could be transferred to other countries which, like South Africa, grapple with large inequities in socio-economic status and quality of education.